What lessons can surgeons learn from sport? The reflections of a retired athlete. Issue 10 (17th August 2021) - Tapper, Richard
Abstract: Surgery often looks to other domains of high performance such as the airline industry for ideas on how to improve surgical performance however little is written about what surgeons might learn from high performance sport. In this paper I offer some observations and ideas from my experience as an Olympic swimmer which I feel may be applicable to surgery and some thoughts on how these concepts might be introduced.